GOOD HEALTH: SALAK FLAVORED COFFEE DRINK VARIANT AS A MEANS OF MENTAL HEALTH EDUCATION FOR THE YOUNGER GENERATION - Sulistyowati, Yuli; Rizky Ramadhon, Ahmad; Albaz Ulumudin, Muhammad; Eryanto, Aji (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
Sukoharjo is an area in Wonosobo Regency that has the potential as a salak pondoh-producing area. The potential of salak pondoh which is quite good in this area can provide new business opportunities that can improve the economy. A new innovation of processed salak pondoh which can be used as salak powder can be used for aroma and taste to create new variations in processed beverage products, including coffee beverage products. Coffee drinks are a type of drink that is quite in high demand among the younger generation. A variety of coffee drinks combined with salak powder is a new type of coffee drink variant that can provide its own attraction. This reason is the basis for using salak flavored coffee drinks as a means to provide mental health education through the packaging used. This is because mental health education is very necessary among the younger generation to prevent the onset of mental disorders. This salak flavored coffee drink variant product is called Good Health. The way to make Good Health products is starting from the preparation of tools and materials, the manufacture of salak powder, to the manufacture of beverages, packaging, and product storage. In addition to having advantages in the distinctive taste and aroma of salak fruit, this coffee drink also has advantages in the form of unique packaging with quotes in the form of inspirational words that educate mental health